Agregado de valor en mosto de uva aplicando diferentes tecnologías de proceso - Massera, Ariel Fernando; Rojo, María Cecilia; Audero, Gabriela Maria; Paez, Roxana Beatriz; Combina, Mariana; Sari, Santiago Eduardo (Instituto de Tecnología de Alimentos, INTA, 2023)
During the production of concentrated musts and wines, the grape juice comes into contact with with microorganisms that can affect the process and/or alter the product. The industry seeks alternatives that allow them to reduce the use of antimicrobials¹. microwaves allow to reduce the microbial load without affecting the nutritional characteristics of the food ². The objective was to evaluate the effect of microwaves on the microbiological characteristics and physicochemical characteristics of the musts of different grapes used to obtain concentrated musts and wines.